In Paranoid Style: The Last Days of Trump. Issue 1 (2nd January 2021) - Rhode, Benjamin
Abstract : Donald Trump's presidency demonstrated that the paranoid style in American politics, as identified by Richard Hofstadter in 1964, is no longer submerged.